Design Analysis of a Foldable Wheel Clamp - MOHDBAKRI, MUHAMMAD IZZUDIN BIN MOHD BAKRI; HJ. ABD KHALIL BIN ABD RAHIM (Research Progress in Mechanical and Manufacturing Engineering, 2026)
This project aims to design and develop a foldable wheel clamp that addresses the common limitations of traditional immobilization devices, such as excessive weight, bulkiness, and lack of adjustability. Conventional clamps, typically constructed from heavy steel or cast iron, are cumbersome to transport and often damage alloy wheels during installation and removal. To overcome these shortcomings, the proposed design incorporates lightweight, high-strength materials, an ergonomic form factor, and a telescopic adjustment mechanism compatible with wheel diameters ranging from 14 to 18 inches. A scissor-type folding mechanism enables compact storage, while a linear actuator automates deployment, achieving full extension in approximately 5 seconds. Rubberized contact pads are integrated to prevent wheel surface damage during clamping.The design methodology encompasses conceptualization, functional decomposition, material selection, and iterative validation using Computer-Aided Design (CAD) and Finite Element Analysis (FEA). The concept was evaluated through a weighted decision matrix prioritizing security, portability, and ease of use. Results indicate that the foldable wheel clamp offers significant improvements in robustness, weight reduction, and ergonomic handling, thereby decreasing the time and physical effort required for deployment. Primarily intended for law enforcement and parking enforcement applications, the design presents a modern, user-centric solution for vehicle immobilization. Future work may explore integration with smart locking systems and field validation of the motorized deployment mechanism under real-world conditions.